Observations about the Effects of Animated Cartoons on Children in View of Mothers and their Intervention Strategies - Hussain, Mudassar; Saif, Sana; Saeed, Robina (Annals of Human and Social Sciences, 2025)
This study explores children’s engagement with animated cartoons and reserachers the intervention strategies used by mothers. Childrens’ mothers may use different staregies based on their observations concerning viewing these animated cartoons, therefore, the the gap is filled by analyzing these observations. The purposive sampling technique is used to select mothers of children between the ages of 5 and 8 years in Lahore. The focus group method was used to collect data from the mothers of 11 boys and 9 girls. The most popular animated cartoons among children are Motu Patlu. The time that children spend viewing animated cartoons increases on weekends. The most preferable media for viewing animated cartoons are smartphones. Irrespective of gender, the mothers involve their children in household work and use storytelling techniques and art to make their children busy. Mothers may involve children in house hold work.